Undifferentiated oligophrenia in the offspring of the in-utero exposed Techa riverside residents - S. A. Shalaginov; A. V. Akleyev (Радиационная гигиена)
The objective of the work was to study the prevalence of undifferentiated oligophrenia in the offspring of antenatally exposed parents. The analysis included 2,908 offspring of the Techa River antenatally exposed residents within Chelyabinsk Oblast born in the period 1974-1992. 1,705 of them were born to an antenatally exposed mother, 1,668 – to an antenatally exposed father, and 368 – to both antenatally exposed parents. Mean in-utero dose for the cohort of in-utero exposed population was 5.8 mGy, while the mean dose of mothers of oligophrenic persons was 12.6 mGy, and that of antenatally exposed fathers – 5.3 mGy. It was found that the prevalence of oligophrenia of different degrees of severity compared to the control group, which included the offspring of unexposed persons of the same age, ethnicity and living in adjacent territories, tends to increase More than 20% of cases of moderate oligophrenia in both main and control groups were of familial nature. All cases of severe oligophrenia in the compared groups were sporadic. There was an increase (p<0.05) in the prevalence of severe oligophrenia when compared to the control group in the offspring cohort of antenatally exposed individuals, 0.45% and 0.24%, respectively, which was 0.59%, p<0.01, in the offspring of exposed mothers. The corresponding rates for the offspring of antenatally exposed fathers were 0.42% and 0.24% in the main and control groups, respectively, p>0.05. No dependence of the prevalence of oligophrenia on the maternal and paternal in-utero dose has been detected.